Effect of regional baric systems on the occurrence of bi- oclimatic conditions in Poland - Tomczyk, Arkadiusz M.; Bednorz, Ewa; Szyga-Pluta, Katarzyna; Owczarek, Małgorzata (Quaestiones Geographicae, 2023)
The present study concerns the determination of the characteristics of bioclimatic conditions, as well as the synoptic situations related to the occurrence of thermal stress conditions, in Poland. The study was based on daily data obtained from the Institute of Meteorology and Water Management – National Research Institute from the period 1966–2020 for 37 synoptic stations in Poland. Based on the obtained data, values of the Universal Thermal Climate Index (UTCI) were calculated. The occurrence of heat stress increases from the north to the south, corresponding with the variability of influx of solar radiation, and is modified by factors at a smaller spatial scale. The results of this paper evidently point to the cooling effect of the waters of the Baltic Sea. In circulation conditions favouring strong and very strong heat stress, e.g. in two of the designated circulation types (T1 and T2), the occurrence of an expansive high-pressure ridge in the Atlantic-European area is typical, stretching from the region of the Azores High towards the north- east, with a secondary high developed within its boundaries. In the third of the designated circulation types (T3), the high-pressure area extends from the Azores eastwards, reaching the Black Sea. Each of the three circulation patterns associated with the unfavourable biometeorological conditions of very strong and extreme cold stress in Poland is characterised by strong pressure centres formed in the Euroatlantic region, triggering the airflow from the northern (T4) or eastern (T5, T6) sector.